Thermodynamic and Transport Properties of Binary Liquid Mixtures of Propyl Acetate with Normal Alkanols at Different Temperature - S. Desale, Bhatu (Asian Journal of Chemistry, 2010)
The density and viscosity of liquid mixtures plays an important role in finding their heat content, mass transport, fluid flow and molecular structure etc. The thermodynamic and transport properties generally yield a valuable information regarding the molecular interactions in pure liquid as well as in liquid mixtures. The study of thermodynamic properties such as enthalpy of activation, entropy of activation and free energy of activation, excess parameters such as excess molar volume (VE), deviation in viscosity (Dh) of binary liquid mixtures is useful in understanding the nature of intermolecular interactions between two liquids. The thermodynamic parameters and excess molar volumes have been calculated from the experimental value of densities and viscosities of binary mixtures of propyl acetate with alkan-1-ols at (298.15, 303.15, 308.15 and 313.15 K). All the mixtures exhibited endothermic enthalpies which decreased with increasing concentration of propyl acetate. The excess molar volumes are fitted to Jouyban- Acree model for correlating the density and viscosity of liquid mixtures at various temperatures. Excess properties considered and yielded acceptable results.